MicroRNAs in CD4+ T cell subsets are markers of disease risk and T cell dysfunction in individuals at risk for type 1 diabetes. (April 2016) - Zhang, Yuxia; Feng, Zhi-Ping; Naselli, Gaetano; Bell, Fiona; Wettenhall, James; Auyeung, Priscilla; Ellis, Justine A.; Ponsonby, Anne-Louise; Speed, Terence P.; Chong, Mark M.W.; Harrison, Leonard C.
Abstract: MicroRNAs (miRNAs) regulate T cell development and function and the disruption of miRNAs in natural regulatory CD4 + FOXP3 + T cells (nTreg) leads to autoimmune disease in mice. To investigate miRNA expression in relation to autoimmune disease risk in humans we sequenced them in purified CD4 + T cell subsets from individuals at high risk of type 1 diabetes (pre-T1D), as well as other healthy individuals. Differences in miRNA expression patterns were observed between specific T cell subsets and, within subsets, between pre-T1D and healthy individuals. Compared to healthy, naive CD4 + T cells in pre-T1D displayed 32 differentially expressed miRNAs, potentially a template for altered miRNA expression in effector memory T cells in T1D. Naive nTreg in pre-T1D displayed two differentially expressed miRNAs, Let-7c and miR-15a. In contrast, nTreg activated in vivo displayed a large number of differentially expressed miRNAs, revealing a pro-inflammatory and FOXP3-repressive signature. Differential expression of specific miRNAs was also a signpost to altered T cell function. For example, in pre-T1D, increased expression of miR-26a in nTreg activated in vivo or in vitro was associated with decreased expression of its target, the histone methyltransferase EZH2 . Chemical inhibition of EZH2 decreased the number of activated naïve nTreg and their expression of nTreg signature genes FOXP3 and TIGIT. Our findings demonstrate that miRNAs differentially expressed in CD4 + T cell subsets are markers of risk and T cell dysfunction in T1D. Highlights: miRNAs are differentially expressed in CD4 + T cell subsets. miRNAs in naïve T cells may reflect altered effector function in pre-T1D. Environment may shape miRNA expression in nTreg in pre-T1D. Increased miR-26a decreases EZH2 and FOXP3 expression in nTreg in pre-T1D.